Oxidative stress in cigarette smoker and smokeless tobacco user among ethnic group north-eastern population of Uttar Pradesh, India - Supriya, K.; Chaudhary, Janardan; Shamal, S. N. (International Journal of Research in Medical Sciences, 2017)
Background: Cigarette smoking and other form of tobacco abusing habits are high prevalence in India at present which can be compare the oxidative level among them. This study aimed to measure the oxidative level among different cigarette smoke and other form of users in north-eastern, Uttar Pradesh of India. Methods: Total of 934 male and female subjects were selected in which 387 were controls (Group I), 140 were active smokers (Group II), 105 were passive smokers (group III), 182 were tobacco users (Group IV) and 120 were active smokers plus tobacco users (group V). Cigarette smoker and tobacco user prevalence <10/day, >10/day for 5 years’ duration were collected. MDA, SOD, GR and CAT were measured. Results: Cigarette smoker and tobacco user prevalence is high in >10 cigarette/day for 5 years, Mean and SD value in oxidative stress in cigarette smokers and tobacco users MDA level 1314±330.1µmol/mg is increased, whereas SOD, GR and CAT level 2.229±0.248 units/ml, 0.0152±0.0071mg/ml and 0.345±0.046mg/ml respectively were reduced in active smoker plus tobacco users. Conclusions: Present study concluded that cigarette smoker and tobacco user showed their increased MDA and decreased SOD, GR and CAT which represented the significantly increased oxidative stress in north-eastern of Uttar Pradesh, India.